Employers' Role in Employee Health: Why They Do What They Do. Issue 11 (November 2020) - Pfeffer, Jeffrey; Vilendrer, Stacie; Joseph, Grace; Kim, Jason; Singer, Sara J.
Abstract : Objective: Employers affect the health of employees and their families through work environments and employee benefits. We sought to understand employer decisions around those topics. Methods: Interviews with 21 executives from diverse, purposely-sampled, progressive companies with transcripts analyzed using inductive and deductive methods. Results: Companies often viewed keeping employees healthy primarily as a means to profitability rather than an end in itself and rationalized stressful workplaces as necessary and non-changeable. Many possible actions including job redesign and changing benefits administrators were seen as infeasible. Even large, resource-rich organizations were strikingly non-agentic. Conclusions: Companies seem less committed to the goal of increasing employee health than they claim or than they should be, given the significant relationship between employee health and economic performance, and see external and internal barriers to improving health that are often self-created. Abstract : Supplemental Digital Content is available in the text